The effect of renal diet in association with enalapril or benazepril on proteinuria in dogs with proteinuric chronic kidney disease - Zatelli, A. (Open Vet J, 2016)
Treating proteinuria in dogs reduces the progression of chronic kidney disease (CKD); renal diets and angiotensin-converting enzyme (ACE)-inhibitors are cornerstones of treatment. Whether different ACE-inhibitors have distinct kidney protective effects is unknown; it is therefore hypothesized that renal diets and enalapril or benazepril have different beneficial effects in proteinuric CKD dogs. Forty-four dogs with proteinuric CKD (IRIS stages 1-4) were enrolled in the study and were fed renal diet for 30 days. Thereafter, they were randomly assigned to one of 2 groups. Dogs in group A (n=22) received enalapril (0.5 mg/kg, q12h) and in group B (n=22) benazepril (0.5 mg/kg, q24h); in both groups, dogs were fed the same renal diet. After randomization, dogs were monitored for 120 days. Body weight and body condition score (BCS), serum concentrations of creatinine, blood urea nitrogen (BUN), albumin and total proteins, and urine protein-to-creatinine (UPC) ratio were compared at different time-points. After 30 days of renal diet, creatinine, BUN and UPC ratio decreased significantly (p<0.0001). Compared to randomization, body weight, BCS, albumin, total proteins, creatinine and BUN did not vary during follow-up in the 44 dogs and differences between group A and B were not observed. However, the UPC ratio of group A at day 60, 90 and 150 was significantly lower than in group B and compared to randomization (p<0.05). In group B it did not vary overtime. It is concluded that the renal diet is beneficial to decrease creatinine, BUN and UPC ratio in proteinuric CKD dogs. Enalapril further ameliorates proteinuria if administered along with renal diet.